Treatment of autism spectrum disorder : evidence-based intervention strategies for communication & social interactions - Prelock, Patricia A.; McCauley, Rebecca Joan, 1952- (Baltimore : Paul Brookes Publishing Co., 2021)
"The new edition of this practical accessible text introduces preservice SLPs to 12 evidence-based interventions that improve the communication and social skills of people with autism spectrum disorder"--
Includes bibliographical references and index.
Keywords: Autism spectrum disorders -- Treatment; Autism spectrum disorders in children -- Treatment